The influence of filler metal on porosity formation of AA6061 aluminium alloy joints - M.F.A, Ibrahim; A.A.A., Aziz; Azman, Jalar; J., Syariff; M.N., Rashdi (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.